Multilevel modeling of retention and disinfection efficacy of silver nanoparticles on ceramic water filters - Mikelonis, Anne M.; Lawler, Desmond F.; Passalacqua, Paola (The Science of the total environment, 2016)
This research examined how variations in synthesis methods of silver nanoparticles affect both the release of silver from ceramic water filters (CWFs) and disinfection efficacy. The silver nanoparticles used were stabilized by four different molecules: citrate, polyvinylpyrrolidone, branched polyethylenimine, and casein. A multilevel statistical model was built to quantify if there was a significant difference in: a) extent of silver lost, b) initial amount of silver lost, c) silver lost for water of different quality, and d) total coliform removal. Experiments were performed on location at Pure Home Water, a CWF factory in Tamale, Ghana using stored rainwater and dugout water (a local surface water). The results indicated that using dugout vs. rainwater significantly affects the initial (p-value 0.0015) and sustained (p-value 0.0124) loss of silver, but that silver type does not have a significant effect. On average, dugout water removed 37.5μg/L more initial silver and had 1.1μg/L more silver in the filtrate than rainwater. Initially, filters achieved 1.9 log reduction values (LRVs) on average, but among different silver and water types this varied by as much as 2.5 LRV units. Overall, bacterial removal effectiveness was more challenging to evaluate, but some data suggest that the branched polyethylenimine silver nanoparticles provided improved initial bacterial removal over filters which were not painted with silver nanoparticles (p-value 0.038). [Display omitted] •Multilevel modeling is useful for analysis of environmental data.•Ag NP stabilizer does not significantly affect total Ag release from CWFs.•Water type significantly affects the release of total Ag from CWFs.•BPEI silver nanoparticles may provide improved coliform removal.